Unsteady blood flow with nanoparticles through stenosed arteries in the presence of periodic body acceleration - Jamil, Dzuliana Fatin; Roslan, Rozaini; Abdulhameed, Mohammed; Che-Him, Norziha; Sufahani, Suliadi Firdaus; Mohamad, Mahathir; Kamardan, Muhamad Ghazali (2018)
The effects of nanoparticles such as Fe304,Ti02, and Cu on blood flow inside a stenosed artery are studied. In this study, blood was modelled as non-Newtonian Bingham plastic fluid subjected to periodic body acceleration and slip velocity. The flow governing equations were solved analytically by using the perturbation method. By using the numerical approaches, the physiological parameters were analyzed, and the blood flow velocity distributions were generated graphically and discussed. From the flow results, the flow speed increases as slip velocity increases and decreases as the values of yield stress increases.